PEMANFAATANZPT AIR KELAPA DAN POC LIMBAH CAIR TAHU UNTUK PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Nurman, Nurman; Zuhry, Elza; Dini, Isna Rahma (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to observe the effect of coconut water GR and LOF of tofu liquid waste, and to get the best concentration on the growth and production of red onion (Allium ascalonicum L.). The experiment was conducted in experimental garden of Agricultural Faculty of Riau University, Pekanbaru. The study lasted for 3 months from July to September 2016. This experiment was conducted experimentally using a Factorial Randomized Complete Random Design (RAL) consisting of 2 factors and 3 replications.Factor I is the concentration of coconut water, consisting of 4 levels ie: A0 = 0%, A1 = 25%, A2 = 50%, A3 = 75%. Factor II is the concentration of tofu liquid waste, consisting of 4 levels ie: L0 = 0%, L1 = 25%, L2 = 50%, L3 = 75%. Of the two factors above, there is a combination of 16 treatments, each repeated 3 times so that there are 48 experimental units. Parameters observed were Number of leaves per clump (tuber), Number of tubers per clump (fruit), largest tuber of tuber per clump (cm), weight of fresh bulb per clump (g), weight of fresh tubers / m2 (g) and weight of dried bulbs / M2 (g). The data obtained were analyzed statistically using vocabulary, then continued by Duncan multiple-range test at 5% level.Giving of GR coconut water and LOF of wastewater know to increase the growth and production of shallot crop. Giving GR of coconut water concentration of 50% and 75% with LOF of wastewater know concentration of 75% is the best concentration in obtaining fresh bulb weight per m2 and weight of dry bulb per m2. Keywords: Red onion, coconut water, Liquid waste tofu